Enterovirus 71 outbreak in Northern Sydney, 2013: Case series and initial response. (July 2014) - Horsley, Emily; Just, E; Torres, C; Huhtinen, E; Forssman, B; Slade, R
<x xml:space="preserve">Abstract</x> Aim Enteroviruses are a common cause of childhood disease which may manifest in a variety of ways. Enterovirus 71 (EV71) is a subtype of enterovirus which can cause meningoencephalomyelitis resulting in neurological sequelae including lethargy, weakness, ataxia, sleep myoclonus, urinary retention and, in severe cases, cardiorespiratory collapse due to neurogenic pulmonary oedema. EV71 was responsible for outbreaks in South East Asia in 1997–1998, in Western Australia in 1999 and in Sydney in 2000–2001. In 2013, we are experiencing another EV71 outbreak in Sydney. This study describes the discovery of a new outbreak in Sydney's Northern Beaches, the clinical findings as well as the public health response. Methods Thirty‐seven children in total presented with presumed EV71 to the Northern Beaches Health Service from December 2012 to April 2013. Most children presented with a prodrome lasting 2–7 days prior to seeking medical attention. Sleep myoclonus was a common presenting sign occurring in 65%. Neurological signs were subtle in the majority of children and were at times missed by clinicians on a child's first presentation. Forty‐six per cent of children who presented to Northern Beaches Health Service during this outbreak required a transfer to a tertiary paediatric centre for more intensive care. Results The public health investigation was important in establishing that the disease was widespread throughout the community and not as a result to exposure to a single child care setting. Identification of risk factors enabled more targeted communication to medical practitioners, child care centres and parents within the local community. Conclusions EV71 is in Australia and all clinicians seeing children in primary, secondary and tertiary care centres need to be aware of the disease, the subtle nature of initial symptoms and the potentially devastating consequences.